1978
DOI: 10.1136/adc.53.7.564
|View full text |Cite
|
Sign up to set email alerts
|

Neurological sequelae in newborn babies after perinatal asphyxia.

Abstract: (Scott, 1976;Thomson et al., 1977), making it more difficult to identify the precise role of asphyxia in causing brain damage. The present study was undertaken in a set of neurologically abnormal babies with a history of fetal distress in labour, to find out whether the types of neurological signs exhibited by such babies have any bearing on their outcome in later infancy or childhood. MethodsSubjects. Newborn babies, 37 to 44 weeks' gestational age, with a history of fetal distress, were diagnosed as severely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Autopsy was performed in 9 of the 15 babies who died and the findings were divers ranging from two with hyaline membrane disease, amniotic fluid aspiration, meconium aspiration, and subarachnoid haemorrhage. Most deaths occurred within the first 24 hours of life, a finding similar to that of several other researchers (16,25).…”
Section: Immediate (≤48 Hours) Outcome Of Babies With Lowsupporting
confidence: 89%
See 1 more Smart Citation
“…Autopsy was performed in 9 of the 15 babies who died and the findings were divers ranging from two with hyaline membrane disease, amniotic fluid aspiration, meconium aspiration, and subarachnoid haemorrhage. Most deaths occurred within the first 24 hours of life, a finding similar to that of several other researchers (16,25).…”
Section: Immediate (≤48 Hours) Outcome Of Babies With Lowsupporting
confidence: 89%
“…Previous studies have documented similar findings (17,24). Cardiovascular complications such as hypotension and bradycardia were present as have been observed by other workers (25,26).…”
Section: Immediate (≤48 Hours) Outcome Of Babies With Lowsupporting
confidence: 86%
“…2 12 17 18 Had we failed to make this distinction we would have concluded that caesarean section had no effect on the risk of newborn encephalopathy. When we applied the eligibility criteria for elective sections we found that eligible case infants were more than 20 times less likely to be delivered by elective section than eligible control infants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also report more severe neurological signs in patients suffering severe HI compared to those with milder HI injury ( Robertson and Finer, 1985 ). Yet, many individuals who showed abnormal neurological signs at birth were normal at 2-year follow-up ( De Souza and Richards, 1978 ). Clinical features and outcomes of neonatal HI are summarized in Figure 1 .…”
Section: Introduction: Global Clinical Impact Of Neonatal Hypoxia Iscmentioning
confidence: 99%